Anti-Inflammatory Properties of Statin-Loaded Biodegradable Lecithin/Chitosan Nanoparticles: A Step Toward Nose-to-Brain Treatment of Neurodegenerative Diseases - Clementino, Adryana Rocha; Marchi, Cinzia; Pozzoli, Michele; Bernini, Franco; Zimetti, Francesca; Sonvico, Fabio (Frontiers in Pharmacology, 2021)
Nasal delivery has been indicated as one of the most interesting alternative routes for the brain delivery of neuroprotective drugs and the application of nanocarriers has been indicated as a promising strategy for the delivery of neurotherapeutics across the nasal epithelia. In this work hybrid lecithin/chitosan nanoparticles were proposed as a drug delivery platform for the nasal administration of simvastatin (SVT-LCN) in view of the treatment of neuroinflammatory diseases. The nanoparticle modulation of simvastatin interaction and transport across the nasal epithelium was investigated, as well as the efficacy of SVT-LCN in suppressing cytokine release in a cellular model of neuroinflammation. Drug release studies were performed in simulated nasal fluids to investigate nanoparticles simvastatin release in conditions mimicking the physiological environment present in the nasal cavity. It was observed that nanoparticles interaction with a simulated nasal mucus decreased nanoparticles drug release and/or slowed drug diffusion. Nevertheless, it was also evidenced the potential effect of two antibacterial enzymes present in the nasal secretions, i.e. lysozyme and phospholipase A2, in promoting drug release from the nanocarrier. Indeed, an enzyme-triggered drug release was observed even in the presence of the mucus, with a 5-fold increase in drug release from LCN. Moreover, chitosan-coated nanoparticles enhanced simvastatin permeation across a human cell model of nasal epithelium (x11). The nanoformulation pharmacological activity was assessed using a “glial-like” cell model, obtained activating the human macrophage cell line THP-1 with LPS as pro-inflammatory stimulus. SVT-LCN were demonstrated to produce to a more pronounced suppression of the pro-inflammatory signaling compared to the simple drug solution (-75% for IL-6 and -27% for TNF- vs. -47% and -15% at 10 µM concentration for SVT-LCN and SVT solution, respectively). Moreover, neither cellular toxicity nor pro-inflammatory responses were evidenced for the treatment with the blank nanoparticles even after 36 hours of incubation, indicating a good biocompatibility of the nanomedicine components in vitro. In reason of their biocompatibility and ability to promote drug release and absorption at the biointerface, hybrid LCN nanoparticles appears as an ideal carrier to achieve nose-to-brain delivery of poorly water-soluble drug such as simvastatin.